2005
DOI: 10.1007/s11663-005-0009-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cooling rate on the solidification of INCONEL 718

Abstract: The superalloy INCONEL 718 (IN718) is a commonly used material in aerospace and turbine components. The advantage of this type of material with sluggish precipitation-hardening kinetics is that IN718 is readily weldable. Both wrought and cast parts are used and welded together. While the alloy has been studied previously, new production processes such as laser treatment demand better knowledge of the solidification process in IN718, especially at high cooling rates. In this investigation, the solidification pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(80 citation statements)
references
References 12 publications
3
74
0
2
Order By: Relevance
“…Amine et al [29] estimated the cooling rates between the newly and previously deposited stainless steel layers, fabricated by laser melting deposition (LMD) process, to be ranging from 200 to 5500 °C/s. Good metallurgical bonding between new and old deposited layers that can be seen in Figure 7 indicates that the instantaneous thermal energy generated from laser power was not only enough to melt the IN718 powder above its melting temperature (1340-1364 °C [30]), but it was also high enough to melt the previously solidified layers. Figure 1a shows the structure of the as SLM-printed IN718 alloy in the center of the cylindrical specimen.…”
Section: Microstructure Of the As-received Powdermentioning
confidence: 97%
“…Amine et al [29] estimated the cooling rates between the newly and previously deposited stainless steel layers, fabricated by laser melting deposition (LMD) process, to be ranging from 200 to 5500 °C/s. Good metallurgical bonding between new and old deposited layers that can be seen in Figure 7 indicates that the instantaneous thermal energy generated from laser power was not only enough to melt the IN718 powder above its melting temperature (1340-1364 °C [30]), but it was also high enough to melt the previously solidified layers. Figure 1a shows the structure of the as SLM-printed IN718 alloy in the center of the cylindrical specimen.…”
Section: Microstructure Of the As-received Powdermentioning
confidence: 97%
“…As the γ growing, segregation of Nb in the remaining liquid would trigger another eutectic reaction L→γ+Laves to terminate solidification, since the available C at this stage is not enough for L→γ+NbC reaction. Antonsson et al [36] compared the effects of cooling rate on IN718's solidification sequence, and suggested that:…”
Section: Solidification Metallurgymentioning
confidence: 99%
“…The HIPing temperatures used are 1140°C, 1180°C, 1210°C, 1260°C and 1275°C. The first two are respectively below and above the Laves phase incipient melting point (between 1150°C and1160°C) of the as-cast Inconel 718 [19]; the third is below the temperature for carbide to begin to dissolve [20]; the fourth and the last are respectively at and above the solidus [20]. Pressurizing and heating during the HIP operation were conducted simultaneously in a QIH-15 mini-hipper.…”
Section: Materials and Experimentsmentioning
confidence: 99%